Morphology of the shell and encrusting microbiota of particles on Scaliola cf. glareosa from the Arabian Gulf. (2nd January 2019) - AlShuaibi, Arafat; Mahmoud, Huda
ABSTRACT: Taxonomical descriptions of gastropods result from studies on shells, particularly for microgastropods, using scanning electron microscopy (SEM) which can provide remarkable details. Scaliola spp., which are characterised by a unique pattern of adhered sand/silt particles (platelets) on the shell exterior, provide an excellent group to investigate the features of microgastropods. The morphology and microstructure of 300 specimens of Scaliola cf. glareosa collected in Kuwait's marine area were investigated using light microscopy and SEM. The microbial communities living within and coating the shells were identified using a PCR-denaturing gradient gel electrophoresis-sequencing method. Results indicated that S. cf. glareosa thrive in sandy mud and silty mud sediments and the direct relationship found between shell whorls and platelet size suggests that this species selectively picks material from marine and allochthonous sediments. The microbial community on Scaliola ( Bacillus sp., Pseudomonas sp. and Micrococcus sp.) adheres platelets to the shell exterior by a mucilaginous gel. It is proposed to include the results found in the present study in a revised definition of the genus Scaliola, as they provide better insight into its Maastrichtian ancestors. However, further field observations and experimental studies need to be carried out to better understand the adhesion process.